Variable step 2-point block backward differentiation formula for index-1 differential algebraic equations - Abasi, Naghmeh; Suleiman, Mohamed; Ibrahim, Zarina Bibi; Musa, Hamisu; Rabiei, Faranak (Science Society of Thailand, 2014)
In this paper, index-1 differential algebraic equations have been solved via a block backward differentiation formula (BDF) using variable step size. Two solution values are obtained simultaneously based on the method in the block. The strategy of controlling the step size is proposed. The method is compared with the existing variable step BDF method. Numerical results are given to support the enhancement of the method in terms of accuracy.